Can Uterine Septum be an Etiological Factor for Dysmenorrhea in Primary Infertile Patients? - Batuhan Turgay; Yavuz Emre Şükür; Batuhan Özmen; Murat Sönmezer; Bülent Berker; Ruşen Aytaç; Cem Somer Atabekoğlu (Journal of Investigative Surgery)
Background The aim of this study is to investigate the association between uterine septum and dysmenorrhea and to assess the effect of hysteroscopic resection on the severity of dysmenorrhea.Method The study group (N:50) consisted of women who underwent hysteroscopic septum resection, and the control group (N:74) consisted of women who underwent diagnostic hysteroscopy and had no significant uterine pathologies. The presence and severity of dysmenorrhea were assessed by using a 10 cm visual analog scale (VAS). The main outcome measurement was the difference between preoperative and postoperative dysmenorrhea VAS scores.Results The mean preoperative VAS score was significantly higher in the study group than the control group (4.6 ± 2.6 cm vs. 3.2 ± 2.4 cm, respectively; p = 0.023). The rates of moderate to severe dysmenorrhea were 52% in the study group and 17.5% in the control group (p = 0.025). The mean dysmenorrhea VAS score of women with uterine septum was significantly improved in postoperative 3rd and 6th months when compared to the preoperative period (3.4 ± 2.4 cm and 3.1 ± 2.3 vs. 4.6 ± 2.6 cm, respectively; P1 = 0.025 and P2 = 0.003).Conclusions Uterine septum seems to be an etiological factor for dysmenorrhea. Although there is no significant relationship between septum depth and dysmenorrhea severity, hysteroscopic resection of the uterine septum improves dysmenorrhea in the infertile study group.